The effect of special exercises on the motor compatibility of fencing players of different ages (13-15) years (Journal of the College of Basic Education, 2022)
The study aimed to prepare special exercises to develop the motor compatibility of fencing players at the ages of (13-15) years, and to know the impact of these exercises on developing motor coordination. The experimental approach was used by designing (equal groups) to suit the nature of the problem.